International And National Mechanisms for Ensuring Human Rights - Oqmamatova Shakhribonu Zafarjonovna (Genius Journals, 2024)
This article provides information about human rights, their protection and provision, as well as international, regional and national mechanisms as a means of ensuring them. Problems in the protection of human rights are presented and scientifically based solutions are described for these issues. Analysis, synthesis, observation, comparison methods are widely used in the article. Today, the reform implemented in the Republic of Uzbekistan in the provision of human rights, their importance, goals and tasks are analyzed
Keywords: Human rights; international va national mechanisms; problems